A Proposal for a Web Information Extraction and Question-Answer System - Saias, José (2009)
The Web is part of today's life and offers all kind of content. We present a system that can help the user to extract information from web documents and to find the answer for simple questions in natural language. This work is focused on newspaper articles and it is based on an ontology knowledge representation, natural language processment and a logic-programming framework.